2018
DOI: 10.20944/preprints201812.0055.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution, Habitat Preference, and Management of the Invasive Ambrosia Beetle Xylosandrus germanus (Coleoptera: Curculionidae, Scolytinae) in European Forests with Emphasis on the West Carpathians

Abstract: The black timber bark beetle Xylosandrus germanus (Blandford) is an invasive ambrosia beetle originating from Southeastern Asia that has become successfully established within Europe and North America. Herein, we provide a review of the spread and distribution of this pest of trees and timber across Europe before and after 2000, along with a review of its habitat preferences. Since the spread of X. germanus across Europe has accelerated rapidly post-2000, emphasis is placed on this period. X. germanus was firs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
(71 reference statements)
0
23
0
1
Order By: Relevance
“…Although both deciduous and coniferous species are attacked by these three Xylosandrus spp., reports of damage generally involve thin-barked deciduous species (Ngoan et al 1976;Wright 2012, 2015;Agnello et al 2015;Ranger et al 2015bRanger et al , 2016. Trees ranging in age from sapling to maturity are attacked, but X. crassiusculus and X. germanus will also attack recently cut stumps and logs (Soné et al 1998;Oliver and Mannion 2001;Zach et al 2001;La Spina et al 2013;Wright 2012, 2015;Coyle et al 2015;Reed et al 2015;Ranger et al 2016;Rassati et al 2016aRassati et al , 2020Galko et al 2018). Stems and trunks are preferred over branches by both X. crassiusculus and X. germanus (Reding et al 2010;Ranger et al 2015aRanger et al , 2019.…”
Section: Host Rangementioning
confidence: 99%
“…Although both deciduous and coniferous species are attacked by these three Xylosandrus spp., reports of damage generally involve thin-barked deciduous species (Ngoan et al 1976;Wright 2012, 2015;Agnello et al 2015;Ranger et al 2015bRanger et al , 2016. Trees ranging in age from sapling to maturity are attacked, but X. crassiusculus and X. germanus will also attack recently cut stumps and logs (Soné et al 1998;Oliver and Mannion 2001;Zach et al 2001;La Spina et al 2013;Wright 2012, 2015;Coyle et al 2015;Reed et al 2015;Ranger et al 2016;Rassati et al 2016aRassati et al , 2020Galko et al 2018). Stems and trunks are preferred over branches by both X. crassiusculus and X. germanus (Reding et al 2010;Ranger et al 2015aRanger et al , 2019.…”
Section: Host Rangementioning
confidence: 99%
“…The black timber bark beetle X. germanus is an invasive ambrosia beetle native to East Asia, from the Kuril Islands to Vietnam, presently occurring in Europe, Russia (European and Asiatic Regions), Turkey and North America (Galko et al 2019 ; Dzurenko et al 2020 ; CABI 2019b ; EPPO 2020 ). The species is polyphagous, and the wide range of its host plants includes many ornamentals, forest (broadleaf and more rarely coniferous species) and fruiting trees (Weber and McPherson 1983 ).…”
Section: Introductionmentioning
confidence: 99%
“…The species is polyphagous, and the wide range of its host plants includes many ornamentals, forest (broadleaf and more rarely coniferous species) and fruiting trees (Weber and McPherson 1983 ). Its diffusion across Europe has accelerated since 2000, probably because of climate change and the increased use of wood as packaging material (Galko et al 2019 ). X. germanus is a xylomycetophagous species whose larvae develop freely in the maternal gallery feeding on the fungus growing on the walls; inside mycangia and maternal gallery, fungi of the genus Ambrosiella prevail as symbiotic organisms although many other fungi, yeasts and bacteria can be found (Mayers et al 2015 ; Tuncer et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among ambrosia beetles, the species of the genus Xylosandrus belong to a highly damaging group of Asian tropical origin. In particular, X. germanus (Blandford), X. crassiusculus (Motschulsky) and X. compactus (Eichhoff) are spreading worldwide, invading also temperate areas of southern Europe, including Italy (Galko et al , 2019). The highly polyphagous X. crassiusculus , attacking more than 200 plant hosts (Castrillo et al , 2013), was reported for the first time in Europe since 2003 on Turkey oaks ( Quercus cerris L.) growing in mixed woods in Tuscany.…”
Section: Introductionmentioning
confidence: 99%